2021
DOI: 10.1186/s12959-021-00354-y
|View full text |Cite|
|
Sign up to set email alerts
|

D-dimer for risk stratification and antithrombotic treatment management in acute coronary syndrome patients: a systematic review and metanalysis

Abstract: Background Data on the prognostic role of D-dimer in patients with acute coronary syndrome (ACS) are controversial. Our aim was to summarize current evidence on the association between D-dimer levels and short/long-term poor prognosis of ACS patients. We also investigated the association between D-dimer and no-reflow phenomenon. Methods Systematic review and metanalysis of observational studies including ACS patients and reporting data on D-dimer l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…neutrophils to lymphocytes ratio and D-Dimer, all biomarkers associated with poor prognosis in ACS setting[15][16][17][18][19]. Then, in our population, MI clinical presentation was worse in LF patients.…”
mentioning
confidence: 61%
“…neutrophils to lymphocytes ratio and D-Dimer, all biomarkers associated with poor prognosis in ACS setting[15][16][17][18][19]. Then, in our population, MI clinical presentation was worse in LF patients.…”
mentioning
confidence: 61%
“…Thrombus burden, as measured by circulating D-dimer levels, has been associated with the risk of cardiovascular events, such as myocardial infarction, in a number of populations such as patients with acute coronary syndrome [ 18 ]. A previous study of 98 patients with unrepaired AAA examined by computed tomography reported that participants with AAA thrombus volume above median had an increased risk of cardiovascular events (relative risk 2.8, 95% CI 1.01, 5.24) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several biomarkers play an important role in the risk stratification for recurrent cardiovascular risk in patients with ACS. Biomarkers representing the pathophysiological processes of hemodynamic stress [N-terminal pro-B-type natriuretic peptide (NT-proBNP)] ( 10 ), inflammation [high-sensitivity C-reactive protein (hs-CRP) and fibrinogen] ( 11 , 12 ), activated coagulation (D-dimer) ( 13 ), endothelial activation [uric acid(UA)] ( 14 ), oxidative stress [gamma-glutamyl transferase (GGT)] ( 15 ), as well as lipid disorders[lipoprotein(a) [Lp(a)]] ( 16 ) have been shown to be associated with increased cardiovascular risk in patients with ACS. Moreover, a simultaneous multimarker strategy improved risk stratification compared to the use of individual biomarkers alone in patients with ACS ( 17 20 ).…”
Section: Introductionmentioning
confidence: 99%